The Role Of The Indonesian Government In Increasing The Quantity And Quality Of Sharia Economic Human Resources - Imron Natsir; Eny Triastuti (Publikasi Indonesia, 2024)
Sharia economics in Indonesia has great potential to develop. However, one of the main challenges in developing Sharia Economics is the limited number of competent Human Resources (HR) in this field. This research aims to determine the relationship between the role of the Indonesian government in increasing the quantity and quality of human resources in the Sharia economy. This research uses a mixed method research method. Data was collected through surveys using questionnaires and literature studies. The data that has been collected is then analyzed using a regression test using the SPSS program. The research results show that there is a significant relationship between the role of the Indonesian Government in increasing the quantity and quality of Sharia Economic Human Resources. The Indonesian Government's efforts to increase the quantity and quality of Sharia Economic Human Resources have shown positive results, but there are still several factors that hamper these efforts. Therefore, it is necessary to make several policy recommendations to increase the effectiveness of the Indonesian Government's role in increasing the quantity and quality of Sharia Economic Human Resources.